Enhancing EFL Students’ Reading Comprehension by Applying Small Group Discussion at Higher Vocational Education - Putu Ngurah Rusmawan; Nurhalimah; Muhamad Ari Perdana; Setianingsih, Tri (Journal of Language and Literature Studies, 2024)
At the polytechnic level of vocational education, students learn English as one of the fundamental skills. Improving one's communication abilities is crucial for students seeking higher professional positions in the tourism industry in this age of globalization. This study aims to apply a small group discussion strategy to enhance procedural text reading comprehension. Classroom action research (CAR) was the method used to conduct this study. The four stages were preparation, execution, monitoring, and evaluation. The first cycle's results showed that the students struggled to understand the process material. Among the students, just 53% were able to achieve a score higher than the minimum requirement of 76. Though cycle 2 was successful, there were still issues, such as students who weren't really engaged in their own study. The results of the observation, the questionnaire, and the students' reading scores all verified this. Around 81% of the students were able to meet those success criteria. Students' reading comprehension in the first semester of higher vocational education at the polytechnic was improved through the use of a small group discussion technique.